Pemetaan Informasi Sebaran Bidang Ilmu Pada Skripsi Fakultas Teknologi Pertanian Lulusan IPB University Tahun 2015-2019 Berdasarkan Standar Universal Decimal Classification: Suatu Kajian Bibliometrika - Abdul Rahman Saleh; Sri Rahayu (Jurnal Pustakawan Indonesia, 2020)
Introduction. Agriculture is an important sector for Indonesia. One of the agricultural sub-sectors is industry and agricultural mechanization. Progress in this field cannot be separated from research activities carried out by lecturers, researchers and students. IPB as one of the leading agricultural universities has certainly produced a lot of research in its field. To find out and photograph the research conducted by undergraduate students, this research was conducted. Methods and Data Collection. The sample is limited to the thesis of the last 5 years (2015-2019) which is taken from the IPB repository. Data analysis. Mapping is reviewed based on the UDC Classification. The table was analyzed descriptively and mapped using VosViewer. Results and Discussion. The number of thesis researches of the Faculty of Agricultural Technology, IPB during 2015-2019 is 2,055 titles. The most researched topics were “production and preservation of solid food” totaling 461 studies and the least were “ventilation and air conditioning” and “rubber industry” with only 2 studies each. The most common keyword is "food preservation techniques" with 278 occurrences. The keyword that has the most correlation is "food preservation techniques" with a total of 605 relationships. Keyword analysis using VosViewer is divided into 16 clusters with the largest cluster consisting of 69 keywords. Furthermore, the main supervisor who was the most productive in guiding students was Arif Sabdo Yuwono (31 mentors), while the most productive supervisors were Muhammad Arif Darmawan and Didah Nur Faridah (19 each). Conclusion. The topic of most interest is “production and preservation of solid foods” (461 titles). The most common keyword is "food preservation techniques" with 278 occurrences. The most productive main supervisor is Arif Sabdo Yuwono with a total of 31 students.